2015
DOI: 10.4236/pos.2015.64008
|View full text |Cite
|
Sign up to set email alerts
|

Precise Point Positioning Technique with IGS Real-Time Service (RTS) for Maritime Applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Our results showed that the developed model improves the solution of Easting, Northing, and Up components. Moreover, using the dual-frequency solution as a reference, the uncertainty of the estimated coordinates using both (traditional and developed) models are at 39% confidence level then transformed to 95% confidence level as follows [30]:…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the developed model improves the solution of Easting, Northing, and Up components. Moreover, using the dual-frequency solution as a reference, the uncertainty of the estimated coordinates using both (traditional and developed) models are at 39% confidence level then transformed to 95% confidence level as follows [30]:…”
Section: Resultsmentioning
confidence: 99%
“…Hadas & Bosy (2015) reported that the satellite orbit accuracy of the IGS01 stream was about 5 cm and the satellite clock accuracy was about 0.3 ns and El- Diasty & Elsobeiey (2015) reported that the satellite orbit accuracy was 5 cm and the satellite clock accuracy was 0.5 ns. In previous studies, the result was based on IGS 01.…”
Section: Min-wook Kang Et Al Accuracy Evaluation Of Igs-rts Correctimentioning
confidence: 99%
“…It is transmitted over the internet based on the Networked Transport of RTCM via Internet Protocol (NTRIP) [ 41 ]. In spite of numerous studies to evaluate the performance of real-time PPP with RTS correction products [ 42 , 43 , 44 , 45 , 46 ], there are few studies, to our knowledge, devoted to real-time coseismic displacement retrieval based on TPP method with RTS correction products.…”
Section: Introductionmentioning
confidence: 99%